2020
DOI: 10.20870/productions-animales.2020.33.1.3092
|View full text |Cite
|
Sign up to set email alerts
|

Cinquante années d’amélioration génétique du porc en France : bilan et perspectives

Abstract: Cette synthèse fait le point sur les principales évolutions de l’amélioration génétique du porc en France depuis la loi sur l’élevage de 1966. Elle évoque rapidement les 20 premières années, qui ont fait l’objet d’une synthèse en 1986, puis décrit plus en détail les évolutions ultérieures. Les objectifs de sélection, initialement limités aux caractères de production, se sont complexifiés avec la prise en compte de la qualité de la viande, puis de la prolificité et enfin des aptitudes maternelles des truies. La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Instead, when the collection is old (as in the local breeds MAR or CNL), a negative IDI was obtained, with some extremely low values revealing a significant "kinship gap" between the cryopreserved males and the current population. In pigs, certain commercial lines within a breed are sometimes managed by different breeding companies (Hulsegge et al, 2019;Bidanel et al, 2020), leading to greater genetic distances between some cryopreserved boars and current populations, and thus negative IDI values. For breeds under strong selection (such as HOL or LWF), negative IDI values are the result of rapid genetic gain and a consequent increase in genetic differentiation between cryopreserved sires and current sires.…”
Section: Diversity Indices As a Guide For Using The Collectionsmentioning
confidence: 99%
“…Instead, when the collection is old (as in the local breeds MAR or CNL), a negative IDI was obtained, with some extremely low values revealing a significant "kinship gap" between the cryopreserved males and the current population. In pigs, certain commercial lines within a breed are sometimes managed by different breeding companies (Hulsegge et al, 2019;Bidanel et al, 2020), leading to greater genetic distances between some cryopreserved boars and current populations, and thus negative IDI values. For breeds under strong selection (such as HOL or LWF), negative IDI values are the result of rapid genetic gain and a consequent increase in genetic differentiation between cryopreserved sires and current sires.…”
Section: Diversity Indices As a Guide For Using The Collectionsmentioning
confidence: 99%
“…Since then, similar selection policies have been implemented by many pig breeding organizations. For example, Bidanel et al (2020) described the developments in France as follows: "The increase in farrowing and lactation mortality correlated with the strong increase in litter size led to the replacement, in the breeding goals of Landrace and Large White, of total number born by a combination of number born alive and the number of functional teats (2002). Subsequently, these criteria were completed with litter size at weaning (2010-2014) and with the within-litter average and standard deviation of birth weight ( 2014)" (our translation from French).…”
Section: Genetics Is Part Of the Solution: Modern Multitrait Breeding...mentioning
confidence: 99%
“…Selection evaluation can be carried out to find out whether a selection has resulted in significant genetic changes or not (Bidanel et al, 2020). Silalahi (2017) showed that selection evaluation could be carried out using frozen semen, where frozen semen can be stored for quite a long time, where selection evaluation for 21 years in French Yorkshire pigs showed genetic improvements in production traits but decreased immunity traits.…”
Section: Brief Selection History In Taiwan Pig Populationsmentioning
confidence: 99%